2002
DOI: 10.4049/jimmunol.169.5.2354
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor of Cytokine Signaling 1 Inhibits Cytokine Induction of CD40 Expression in Macrophages

Abstract: CD40 is a type I membrane-bound molecule belonging to the TNFR superfamily that is expressed on various immune cells including macrophages and microglia. The aberrant expression of CD40 is involved in the initiation and maintenance of various human diseases including multiple sclerosis, arthritis, atherosclerosis, and Alzheimer’s disease. Inhibition of CD40 signaling has been shown to provide a significant beneficial effect in a number of animal models of human diseases including the aforementioned examples. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 58 publications
5
55
1
Order By: Relevance
“…In contrast, targeted expression of SOCS-1 in oligodendrocytes protects them against the injurious effects of IFN-␥ (63). Our findings in macrophages/microglia indicate that both SOCS-1 and SOCS-3 attenuate inflammatory events in these cells (35,45,64). Thus, depending on the CNS cell type, SOCS-3 expression exerts beneficial or detrimental effects.…”
Section: Discussionmentioning
confidence: 72%
“…In contrast, targeted expression of SOCS-1 in oligodendrocytes protects them against the injurious effects of IFN-␥ (63). Our findings in macrophages/microglia indicate that both SOCS-1 and SOCS-3 attenuate inflammatory events in these cells (35,45,64). Thus, depending on the CNS cell type, SOCS-3 expression exerts beneficial or detrimental effects.…”
Section: Discussionmentioning
confidence: 72%
“…In the RAW264.7 macrophage cell line, IFN-␥ and TNF-␣ synergize in the activation of NF-B (14,15). In these cells, IFN-␥ synergizes with endogenously produced TNF-␣ to give stronger and more prolonged NF-B activation than does exogenous TNF-␣ treatment or IFN-␥ treatment alone (achieved by the use of a neutralizing anti-TNF-␣ Ab to inhibit signaling by endogenously produced TNF-␣) (14,15).…”
Section: Stat-1␣ and Ifn-␥ As Modulators Of Tnf-␣ Signaling Inmentioning
confidence: 99%
“…In these cells, IFN-␥ synergizes with endogenously produced TNF-␣ to give stronger and more prolonged NF-B activation than does exogenous TNF-␣ treatment or IFN-␥ treatment alone (achieved by the use of a neutralizing anti-TNF-␣ Ab to inhibit signaling by endogenously produced TNF-␣) (14,15). These results prompted us to search for mechanisms by which these two signaling pathways could communicate to enhance NF-B activation.…”
Section: Stat-1␣ and Ifn-␥ As Modulators Of Tnf-␣ Signaling Inmentioning
confidence: 99%
“…Its signaling activity results in the upregulation of pro-inflammatory adhesion molecules (ICAM1, VCAM1, E-selectin and P-selectin) and cytokines and chemokines (IL-1, IL-6, IL-8, IL-12, TNF-alpha and MIP-1alpha) and has been implicated in the pathogenesis of several CNS disorders (71,72). Wesemann et al (70) showed that overexpression of SOCS1 inhibits CD40 expression by preventing STAT1 phosphorylation, suppressing TNF-alpha secretion and the subsequent NF-kappaB activity in macrophages stimulated by IFN-gamma (70).…”
Section: Ppar-gamma-independent-mechanismsmentioning
confidence: 99%